Asia and Pacific Small States : Raising Potential Growth and Enhancing Resilience to Shocks. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2013)
The small states of the Asia and Pacific region face unique challenges in raising their growth potential and living standards. These countries are particularly vulnerable because of their small populations, geographical isolation and dispersion, narrow export and production bases, lack of economies of scale, limited access to international capital markets, exposure to shocks (including climate change), and heavy reliance on aid. In providing public services, they face higher fixed government costs relative to other states because public services must be provided regardless of their small population size. Low access to credit by the private sector is an impediment to inclusive growth. Capacity constraints are another key challenge. The small states also face more limited policy tools. Five out of 13 countries do not have a central bank and the scope for diversifying their economies is narrow. Given their large development needs, fiscal policies have been, at times, pro-cyclical. Within the Asia-Pacific small states group, the micro states are subject to more vulnerability and macroeconomic volatility than the rest of the Asia-Pacific small states.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet